Judge-target trait similarity and accuracy: Does it 'take one to know one'? - Sait, Zaakiyah (Organisational Psychology, 2014)
Accurate personality judgement has become increasingly important in the workplace, as research indicates that other-ratings of personality may be promising predictors of performance. The effect of personality similarity on judgment accuracy presents a novel approach for studying factors associated with accurate judgement. The objective of this study was to investigate the relationship between judge-target personality trait similarity and accuracy in judging personality. It is proposed that judges whom have high levels of a certain trait, are more proficient at detecting and utilising behavioural cues related to the same trait, thereby leading to higher trait judgment accuracy. Previous literature has indicated that demographic similarity between judge and target may contribute to accurate personality judgement. However, there appears to be a lack of research on the effect of personality similarity on judgment accuracy. Survey questionnaires were administered to a convenience sample of 186 university students. The Big Five Inventory was used to measure participants' personality traits, whilst hypothetical personality descriptions of five applicants were used to serve as targets for rating personality. Subject matter experts' ratings were used as ?true scores' for the derivation of accuracy measures for each judge. Finally, we correlated judges' personality traits with accuracy of judging corresponding personality traits, across targets. No significant positive relationships were found between judges' personality trait scores and their judgemental accuracy of corresponding traits across targets. Judges with low levels of a trait, could judge targets with low levels of the same trait just as accurately as those judges with high trait levels, and vice versa. Apparently, cue detection and utilisation for a specific trait is not improved when judges share a particular trait with the target. This study provides organisations with limited empirical findings to inform training or selection of judges, aside from the recommendation that judges of personality may be sensitised about factors influencing their ratings. Contribution/value add: The results of this study indicated that trait expertise does not emanate from being high on the trait being judged. This finding enhances our understanding of the factors that influence judgment accuracy.